The arts and humanities, technology and the 'English Baccalaureate': STEAM not STEM. Issue 2 (16th February 2012) - Welch, Graham F.
The article argues that the music should (a) be a core subject within any revision to the English National Curriculum for schools and also (b) integral to the UK Government's English Baccalaureate where the arts do not feature at all. Such a national policy approach flies in the face of research evidence of the crucial significance of the arts and humanities, including music, in human culture and development. Government policy is also ambiguous concerning its view of technology, either as a curriculum subject or as a tool for learning and creativity. Nevertheless, it is argued that technology is a core feature of our engagement with the arts (including music) and humanities. Their combination offers a vital and rich resource in the education of our young people.